Predicted soil organic carbon (SOC) content (g/kg) and SOC stock (t/ha) in the Eastern Plains of Colombia - Rainford, Shauna-kay; Martin López, Javier Mauricio; Silva, Mayesse Aparecida da (2021)
SOC content (g/kg) and SOC stock (t/ha) at 0-30 cm soil depth maps were developed for the Eastern plains of Colombia at a spatial resolution of 90 m. These maps are part of the results compiled in the paper: “Approximating Soil Organic Carbon Stock in the Eastern Plains of Colombia” and represent the spatial variation of both SOC content and stock at 0-30 cm soil depth. For more details, see Shauna et al, (2021): (doi.org/10.3389/fenvs.2021.685819).